Yahoo Web Search

  1. r +4/ r ^2-1 × r ^2-16/ r +1 = ( r ^3 + 4 - r ^2)/ r ^2 x ( r ^3 - 16 + r )/ r = 1/ r ^3 x ( r ^3 + 4 - r ^2) x ( r ^3 - 16 + r ) = 1/ r ^3 x [ r ^3 x ( r ^3 - 16 + r ) + 4 x ( r ^3 - 16 + r ) - r ^2 x ( r ^3 - 16 + r ...

    1 Answers · Education & Reference · 18/03/2014

  2. | r +s|^2 = ( r +s) dot ( r +s) = | r |^2 + 2 ( r dot s) + |s|^2 Given | r | = 5, and |s| = 3 we have: = 5^2 + 2 ( r dot s) + 3^2 = 34 + 2 ( r dot s) since s is perpendicular to ( r +s), s...

    2 Answers · Science & Mathematics · 18/02/2015

  3. 95.5 = (1/(1+ r )) * (29.4/ r ) = (29.4)/{(1+ r )( r )}; (95.5) {(1+ r )( r )} = 29.4; {(1+ r )( r )} = 29.4/95.5 = 0.30785 r ^2 + r = 0.30785 r ^2 + r - 0.30785 = note that ( r +1/2...

    1 Answers · Education & Reference · 13/11/2007

  4. r = <x, y, z>, || r || = (x^2 + y^2 + z^2)^(-1/2) So, we need to compute curl <...

    4 Answers · Science & Mathematics · 02/03/2011

  5. r ^-3 ln( r )dr u = lnr ; dv = r ^-3dr du = (1/ r )dr ; v = (-1/2) r ^-2 = (-1/2) r ^-2 ln( r ) + ∫(1/2...1/2) r ^-2 ln( r ) + [(-1/4) r ^(-2)] integrate from 1 to infinity = (-1/2) r ^-2 ln( r ) + lim(a->infinity) [(-1/4) r ^(-2)] integrate from 1 to a...

    2 Answers · Science & Mathematics · 23/10/2011

  6. Hi, The DVD+ R and DVD- R are competing ...the formats. However, because the DVD- R format has been in use since 1997, it has...

    4 Answers · Consumer Electronics · 22/02/2007

  7. r solves x^2 + ax + b = 0 => r * r + a* r = -b => ( r +a)* r = -b Since r ,a are integers, -b is an integer multiple of r , and so is b, hence r divides b.

    3 Answers · Science & Mathematics · 03/02/2013

  8. Hello, The DVD+ R and DVD- R are competing ...the formats. However, because the DVD- R format has been in use since 1997, it has...

    2 Answers · Consumer Electronics · 12/02/2008

  9. Multiply by r : 1 - 1/2 r ^2 = 3/5 r 1/2 r ^2 + 3/5 r - 1 = 0 5 r ^2 + 6r - 10 = 0 And solve using the quadratic equation.

    3 Answers · Science & Mathematics · 05/08/2009

  10. [( r -2)( r +9) -2r( r +2)] / [( r +2)( r +9)] = 6 ( r ^2 + 7r -18 -2r^2 - 4r) / [( r +2)( r +9)] = 6 (- r ^2 + 3r - 18) / ( r ^2 + 11r + 18) = 6 - r ^2 + 3r - 18 = 6( r ^2 + 11r + 18) = 6r^2 + 66r + 108 7r...

    1 Answers · Science & Mathematics · 06/05/2010

  1. Try asking your question on Yahoo Answers